A Subtitling Analysis Of Adjective In A Good Day To Die Hard Movie By Syarif Hidayatulloh - Wijayanto, Aryan, Dr. Dwi Haryanti, M.Hum, Muamaroh, Ph. D (2015)
The research paper analyzes adjective in subtitling A Good Day To Day Hard movie. The study aims (1) to classify the translation shifts of adjective in A Good Day to Die Hard movie and (2) to describe the equivalent translation shifts of adjective in A Good Day to Die Hard movie. The type of this research is descriptive qualitative research. The object of the study is the movie entitled A Good Day to Die Hard and its subtitling. The data of this study is clauses and sentences consisting adjective found in A Good Day to Die Hard movie. Data source used in this research are English and Indonesian subtitling of A Good Day To Die Hard movie. Based on the analysis, there are 55 or 83,34% data of adjectives that translated using class shift from 8 variations are covered by Adj1 translated into verb, Adj1 translated into noun, Adj1 translated into adverb, Adj2 translated into noun, Adj2 translated into adverb, Adj2 translated into numerical, Adj3 translated into demonstrative, and Adj4 translated into pronominal. Then, there are 11 data or 16,66% data of adjective that uses translation level shift from variations adjective that translated into adjective phrase and adverb phrase. From 66 data which found in this subtitle, all of the data 100% equivalent. It can be concluded that all of the translation shifts of adjective in A Good Day To Die Hard movie are equivalent.